2013
DOI: 10.1155/2013/507397
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment Methods of Laryngeal Muscle Activity in Muscle Tension Dysphonia: A Review

Abstract: The purpose of this paper is to review the methods used for the assessment of muscular tension dysphonia (MTD). The MTD is a functional voice disorder associated with abnormal laryngeal muscle activity. Various assessment methods are available in the literature to evaluate the laryngeal hyperfunction. The case history, laryngoscopy, and palpation are clinical methods for the assessment of patients with MTD. Radiography and surface electromyography (EMG) are objective methods to provide physiological informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 37 publications
0
14
0
5
Order By: Relevance
“…The group of participants examined in the present study consisted mainly of middle-aged women with hyperfunctional voice patterns, which corresponds to past descriptions in the literature [2, 6, 9]. Voice complaints, such as hoarseness, voice alterations, and excessive effort when speaking, stood out as the most common concerns.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The group of participants examined in the present study consisted mainly of middle-aged women with hyperfunctional voice patterns, which corresponds to past descriptions in the literature [2, 6, 9]. Voice complaints, such as hoarseness, voice alterations, and excessive effort when speaking, stood out as the most common concerns.…”
Section: Discussionmentioning
confidence: 70%
“…First, the study was carried out in an outpatient clinic specialized in otorhinolaryngology, where patients are commonly diagnosed with laryngeal pathologies and referred to speech therapy. Secondly, past research has shown that most patients with MTD have the secondary type, since it is a voice disorder whose medium- to long-term consequence is laryngeal disorders [2, 9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cada uno de estos elementos es sensible a la sobrecarga o al sobreuso que ofrecen agentes mecánicos como la fonación (O'Rourke et al, 2014). Cuando la sobrecarga es intensa o repetitiva, estos tejidos expresan una serie de signos y síntomas vocales, los que incluyen a la odinofonía (Jung et al, 2017) y, en algunos casos, a la aparición de compresión supraglótica (Khoddami, Nakhostin Ansari, Izadi, & Talebian, 2013). Se ha teorizado que la sobreactividad del tirohioideo incide directamente en la aparición de compresión medial (Van Houtte, Van Lierde, & Claeys, 2011).…”
Section: Efectos Sobre La Región Perilaríngeaunclassified